Collaboration for innovation in services - Christiane Hipp (Brandenburg University of Technology Cottbus, Chair of Organization, Human Resource & General Management, 2009)
The research was motivated by the importance of inter-firm collaboration within service innovation. Inter-firm collaboration covers a broad range of organizational combinations of various size and motivations in various levels of formal agreements. The book chapter will explore the choice of different partners and knowledge sources for enabling co-operative innovation activities following the approach of loosely-coupled and institutional networks. The empirical results show different collaborative behavior within different service industries.
Keywords: 330; innovation management; service innovation; collaboration; Unternehmenskooperation; Innovationsmanagement; Dienstleistung